THE BUDDHADHAMMA AND THE SUCCESSFUL AND EFFECTIVE WORK - Prasomsuk, Anontri; Bhavanabodhikun, Phrakhru; Leeka, Jaras; Sariphan, Apinya (Journal of Graduate MCU KhonKaen Campus, 2022)
This academic article aims to present the Buddhadhamma and the successful and effective work. It was found that Iddhipada 4 (4 paths of accomplishment) are the basic Buddhist principles for all accomplishments. These four paths are consistently related and rational process. These are wonderful virtue that supports the success of all works